Cooperation in R&D in the pharmaceutical industry-The network as an organizational innovation governing technological innovation - Starpoli, Carine (Technovation)
The paper sets out to understand the development of the networking form of partners in the pharmaceutical industry where, so far, only two companies have adopted this form of organization.